2021
DOI: 10.1016/j.apsb.2021.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin induces ferroptosis in bladder cancer cells by downregulating FTH1

Abstract: Ferroptosis is a non-apoptotic regulated cell death caused by iron accumulation and subsequent lipid peroxidation. Currently, the therapeutic role of ferroptosis on cancer is gaining increasing interest. Baicalin an active component in Scutellaria baicalensis Georgi with anticancer potential various cancer types; however, the effects of baicalein on bladder cancer and the underlying molecular mechanisms remain largely unknown. In the study, we investigated the effect of baicalin on bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(89 citation statements)
references
References 26 publications
1
88
0
Order By: Relevance
“…Although the anticancer activity of baicalin may involve a pro-oxidant mechanism, these compounds also cause a depletion of the GSH content in human hepatoma cells [ 21 ]. Kong et al [ 22 ] investigated the effect of baicalin on the bladder cancer cells 5637 and KU-19-19 and found that baicalin performed its anticancer activity by inducing apoptosis and cell death in bladder cancer cells. Baicalin-induced ferroptotic cell death in vitro and in vivo, which is accompanied by an accumulation of reactive oxygen species (ROS) and the enrichment of intracellular chelate iron.…”
Section: Discussionmentioning
confidence: 99%
“…Although the anticancer activity of baicalin may involve a pro-oxidant mechanism, these compounds also cause a depletion of the GSH content in human hepatoma cells [ 21 ]. Kong et al [ 22 ] investigated the effect of baicalin on the bladder cancer cells 5637 and KU-19-19 and found that baicalin performed its anticancer activity by inducing apoptosis and cell death in bladder cancer cells. Baicalin-induced ferroptotic cell death in vitro and in vivo, which is accompanied by an accumulation of reactive oxygen species (ROS) and the enrichment of intracellular chelate iron.…”
Section: Discussionmentioning
confidence: 99%
“…A natural product baicalin was found to induce ferroptosis in bladder cancer cells 5637 and KU-19-19 by regulating ferritin heavy chain 1 (FTH1). Intraperitoneally injected Baicalin induced regression of the tumor mass in mice inoculated with KU-19-19 cells (90). Fin56 which is a type 3 ferroptosis inducer promotes GPX4 degradation and triggers ferroptosis in bladder cancer cells.…”
Section: Urologic Cancersmentioning
confidence: 94%
“…Feng et al [ 22 ] used an anti-3F3 ferroptotic membrane antibody (3F3-FMA) to detect ferroptotic cells, discovering that 3F3-FMA is a TfR1 antigen; hence, they concluded that TfR1 accumulation on the cell surface is a feature of ferroptosis. In researching baicalin-triggered ferroptosis in vitro and in vivo, Kong et al [ 23 ] found higher intracellular chelated iron levels after FTH1 overexpression in bladder cancer cells, indicating that baicalin-induced ferroptosis was accelerated by downregulating FTH1 expression. Bao et al [ 24 ] found ferroptosis phenotypes in the brains of Alzheimer’s disease (AD) model mice, and in these mice, ferroptosis was induced by downregulating FPN expression.…”
Section: Main Characteristics Of Ferroptosismentioning
confidence: 99%